Fossils, evidence of vanished worlds - Gayrard-Valy, Yvette (New York : Harry N. Abrams, 1994)
A history of the discovery of fossils, discussing how their analysis helps us to understand the evolutionary roles of various life forms.
Translation of work published by Gallimard in 1987.
Includes bibliographical references (p. 184) and index.
New York Times.
Young Adult
Keywords: Fossils; Fossils